THE HISTORICAL EVOLUTION OF THE INSTITUTION OF HOUSE ARREST AND THE EXPERIENCE OF UZBEKISTAN - Yoqubov, Ulugbek (Oriental Journal of History, Politics and Law, 2025)
The article analyzes the historical formation and evolution of the house arrest institution. The stages of development of this institution from ancient Mesopotamia to modern times, its specific features in various civilizations and legal systems are studied. The formation of the house arrest institution in the Russian Empire, the Soviet period and in independent Uzbekistan is separately examined. The experience of foreign countries and international standards are analyzed, prospects for improving the house arrest institution in national legislation are identified.